An Implementation of Islamic Education Moderation in Indonesia (A Study at Raden Intan State Islamic University of Lampung) - Asrori, Achmad; Sunarto, Sunarto (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
Globalization poses significant challenges to Islamic education in Indonesia, particularly regarding character education and scientific integration. This study aims to investigate the implementation of moderation in Islamic education at UIN Raden Intan Lampung in response to contemporary challenges. This study takes a qualitative approach with a phenomenological design. Data was gathered through interviews, observations, and documentation. The data came from Islamic Education lecturers at UIN Raden Intan Lampung. This study looks at curriculum transformation that combines Islamic and modern science, digital learning, and the internalization of religious moderation values. The study's findings show that the moderation of Islamic education at UIN Raden Intan Lampung focuses not only on intellectual development but also on developing the character of students who are moderate, open, and adaptable to social dynamics. Moderate Islamic education is expected to produce competent and globally competitive graduates while preserving Islamic values based on the principle of moderation.